CHALLENGES DURING THE PANDEMIC: USE OF E-LEARNING IN MATHEMATICS LEARNING IN HIGHER EDUCATION - Muhammad Irfan; Betty Kusumaningrum; Yuyun Yulia; Sri Adi Widodo (Jurnal Infinity, 2020)
On March 16, 2020, many universities in Indonesia began implementing online-based learning to replace lectures in the classroom. This is done as a way to reduce the transmission of the Covid-19 outbreak in Indonesia. There is an opinion that with the implementation of online learning, especially in mathematics education study programs, there are many obstacles when learning takes place. This study aims to determine the obstacles that arise after the implementation of online learning in mathematics learning in Higher Education. This research is a qualitative case study, assisted by an online survey. The researcher collected data through an online survey consisting of 27 questions. The survey is aimed at lecturers who teach in Mathematics Education study programs in Indonesia. The survey contains structured questions and leads to three parts, namely; basic skills challenges, teaching and learning challenges, and university challenges. The 27 questions contained questions about the ability of platform mastery to support online learning owned by each lecturer. The research involved 26 lecturers from universities in Sumatra, Java, Kalimantan, and Sulawesi. The results of this study reveal that all lecturers affected by the pandemic use a Learning Management System (LMS) based website as a means of online learning. The learning management system-based platform is the most widely used (google class and Edmodo) while video conferencing is the second choice (Zoom and Skype). What is interesting is that the LMS available on campus is less attractive to lecturers. However, there are obstacles faced such as the limitations of writing mathematical symbols and the limited basic capabilities of the learning management system and multimedia software to support online learning.